DISEMINASI APLIKASI SI CETAR (APLIKASI LITERASI BERBASIS KEARIFAN LOKAL BLITAR) BERSAMA SEKOLAH DASAR WILAYAH KECAMATAN KANIGORO - Putriani, Ida; Widiastuti, Sripit; Rarasati, Ida Putri (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Literacy activities at the primary school level aim to develop students' interest in reading and reading habits. These activities involve aspects of listening, reading and a variety of types of reading materials. However, their implementation requires a structured program and effective supervision. Preliminary research shows that the main challenges in the current School Literacy Movement are supervision and habituation constraints that are difficult for teachers to observe, as well as limited access to reading resources due to distance learning. This community service aims to make a positive contribution by applying Si Cetar Media (Blitar Story Literacy Application) as a supporting tool for literacy activities in primary schools. The implementation approach involved preparation, workshop and evaluation stages. Initial observations and determining instruments were conducted in the preparation. The workshop involved the school principal and involved the use of Si Cetar Media. The evaluation of the literacy program with Media Si Cetar was conducted in the final stage. Si Cetar Media is expected to have a positive impact on teachers, students and schools. The various titles and storylines accompanied by interesting pictures can motivate students, while easy access through laptop or mobile devices enables independent learning. The use of this media also makes it easier for teachers to manage literacy programs and assess student progress. Furthermore, Media Si Cetar complements the school's collection of reading resources, allowing students to learn through a broader digital platform than traditional libraries. The expected outcomes are teachers' positive response to the Community Service Program (PKM) as well as the effective dissemination of Media Si Cetar.